Concurrent Chagas’ disease and borderline disseminated cutaneous leishmaniasis: The role of amiodarone as an antitrypanosomatidae drug - Alberto E Paniz-Mondolfi; Alexandra M Pérez-Álvarez; Oscar Reyes-Jaimes; Gustavo Socorro; Olga Zerpa; et al (Dove Medical Press, 2008)
Alberto E Paniz-Mondolfi1,4, Alexandra M Pérez-Álvarez1, Oscar Reyes-Jaimes2, Gustavo Socorro1, Olga Zerpa3, Denisa Slova4, Juan L Concepción51Laboratorio de Estudio de Antígenos, Instituto de Biomedicina, “Hospital José Gregório Hernández”, Instituto Venezolano de los Seguros Sociales, Caracas, Venezuela; 2Departamento de Dermopatología, Instituto de Biomedicina, 3Sección de Leishmaniasis, Instituto de Biomedicina, Caracas, Venezuela; 4Department of Pathology and Laboratory Medicine, St. Luke’s – Roosevelt - Beth Israel Medical Center, University Hospital of Columbia University College of Physicians and Surgeons, New York, USA; 5Laboratorio de Enzimología de Parásitos, Facultad de Ciencias, Universidad de Los Andes, Mérida, VenezuelaAbstract: The occurrence of mixed infections of Trypanosoma cruzi and Leishmania spp. is becoming a common feature in Central and South America due to overlapping endemic areas. Unfortunately, the possibilities for treating flagellated kinetoplastid infections are still very limited and most of the available drugs exhibit severe side effects. Although the development of new drugs for Leishmania has markedly improved in the last years, the tendency is still to employ antimonial compounds. On the other hand, treatment for Chagas’ disease is only available for the acute phase with no effective therapeutical options for chronic stage disease. The following case report substantiates the recently discovered effect of amiodarone as a nonconventional antiparasitic drug, particularly against Leishmania, breaching a new perspective in the therapeutic management of these important infectious parasitic diseases.Keywords: Chagas’ disease, leishmaniasis, chemotherapy, amiodarone